Menggugah Motivasi Belajar Siswa melalui Metode Ice Breaking dalam Pembelajaran Fiqih - Sa'adatunnisa, Hilma; Munir, Dede Rizal; Setiawan, Usep (Abdi Widya: Jurnal Pengabdian Masyarakat, 2025)
This study aims to examine the effectiveness of the ice-breaking method in enhancing students' learning motivation in the subject of Fiqh for third-grade students at MI Al-Barokah. Learning motivation is a crucial factor in the success of the learning process, especially in subjects that require conceptual understanding and memorization, such as Fiqh. Ice-breaking, as an effort to create an enjoyable learning experience, is expected to foster a more interactive learning atmosphere and reduce student fatigue. This study employs a qualitative method with a descriptive approach. Data is collected through direct classroom observations during Fiqh lessons. The collected data is analyzed descriptively to identify key themes relevant to the study. As a participant observer, this study aims to examine the impact of ice-breaking activities on students' learning motivation. The results of this study indicate that the ice-breaking method has the potential to enhance students' motivation in learning Fiqh at MI Al-Barokah. Observations reveal that students appear more enthusiastic and actively participate in the learning process after engaging in ice-breaking activities. However, this study also finds that the effectiveness of ice-breaking can vary depending on the type of activity used and how teachers integrate it into the learning process.